Automated Correction for Trace Tables in a CS1 Course - Teubl, Fernando; Zampirolli, Francisco (Anais do Simpósio Brasileiro de Informática na Educação (SBIE); 2023: Anais do XXXIV Simpósio Brasileiro de Informática na EducaçãoDO - 10.5753/sbie.2023.233468, 2023)
This work presents a remote, asynchronous, parametric, and automatically corrected evaluation based on the Trace Table method for an introductory programming course. Moodle was used as the learning platform, VPL as the evaluation module/interface, and MCTest as the test generator. The Trace Table method allows for the analysis of students’ knowledge in pseudocode, without relying on any specific programming language. The answers were formatted in a table, and the evaluations were automatically corrected during the student’s problem-solving process. Two evaluations were applied throughout the course: an intermediate and a final. The course had 309 students and the results indicated a high acceptance rate, with over 80% approval of the method.